African Land Questions, Agrarian Transitions and the State : Contradictions of Neo-Liberal Land Reforms - Moyo, Sam (Book collections on Project MUSE., 2008)
This empirically grounded study provides a critical reflection on the land question in Africa, research on which tends to be tangential, conceptually loose and generally inadequate. It argues that the most pressing research concern must be to understand the precise nature of the African land question, its land reforms and their effects on development. To unravel the roots of land conflicts in Africa requires thorough understanding of the complex social and political contradictions which have ensued from colonial and post-colonial land policies, as well as from Africa's 'development' and capita.